Health System Inquiry: Is Health Sector Reforms in Bangladesh Imperative? - Alam, Mohammed Shadrul; Islam, Shahnoor; Basher, AKM Khairul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
In Bangladesh, Government is trying to find a perfect health system that best serves its population. Here, we present the results of our study with aim to assess the opinion of various stakeholders about: what are the 1) high-priority areas, 2) moderate priority areas, and 3) low-priority areas to reform the health sectors for Bangladesh. We conducted a cross-sectional, exploratory and anonymous population-based e-survey from February to June, 2021 among individuals aged above 26 years. A semi-structured questionnaire was designed and incorporated into the Google survey tool (Google Forms) and a shareable link was generated and disseminated to physicians, Academicians/ Clinicians of Medical Colleges/ Universities, Health System administrators etc. Respondents were also given space to comment on each topic. Comments & reactions of all respondents were categorized into three main headings. These were 1) high-priority areas, 2) moderate priority areas, and 3) low-priority areas to reform the health sectors for Bangladesh. Out of 483 respondents, 476 respondents (80.5% males and 19.5% female) completed the entire survey. The mean age of respondents is 44.70 SD± 10.07 with age range 26-86 years. About 27% of the respondents were from faculties from medical colleges /medical universities and 1.7% were health system administrators. The high prioritized areas where the majority (>60%) of our respondents strongly agreed upon, for instance, good governance, structural referral system should be establishment, and reformation of existing health care procurement & purchasing policy. The moderate prioritized areas where 50 - 60% of our respondents strongly agreed upon, such as securing sustainable financing for health care, further development of existing health infrastructure, and establishment of Health Academy of planning and development (HAPD). The low prioritized areas where less than 50% of our respondents strongly agreed upon, such as decentralization and autonomous health system, public health-oriented infection prevention and control (IPC) program, and implement the national health insurance system (NHIS) under a separate authority etc. Good governance in health departments & health care provider organizations are essential elements for health sector reform. Health sector reform should be sustained, purposeful, planned and evidence-based and fundamental change addressing significant, strategic dimensions of health systems. J Bangladesh Coll Phys Surg 2022; 40: 84-94